The economic contribution of river recreation and tourism in the Little Yampa Canyon, Colorado - Burkard, Matthew, author; Thilmany, Dawn, advisor; Hill, Rebecca, committee member; Bayham, Jude, committee member; Guo, Tian, committee member (Colorado State University. Libraries, 2023)
The Yampa River is a key driver of outdoor recreation and tourism opportunities to the city of Craig, Colorado and the surrounding Moffat County, drawing in river-based recreators and tourists from surrounding areas. So, opportunities to enhance access are important to a region that seeks to further diversify its economic portfolio in light of broader transitions occurring in the energy and agriculture sector. A land acquisition proposal by the Bureau of Land Management seeks to expand public access to the Yampa River and the nearby recreation amenities and improving highway access to the current Little Yampa Canyon Special Recreation Management Area, while protecting additional wildlife habitat and fisheries. The purpose of this research is to collect and analyze outdoor recreation and tourism spending data from resident and non-resident recreators near Craig, Colorado to ascertain one set of potential benefits of such an investment. This research employs an intercept survey at key access points along the Yampa River near the proposed land acquisition to capture recreator information such as dollar amounts spent across common expenditure categories, typical recreation habits, user perceptions of current and proposed recreational resource access and qualities, and demographic information. This paper utilizes an input-output methodology via IMPLAN to produce economic contribution estimates using data received from intercept surveys to quantify both the baseline contribution of recreation near Craig, Colorado and the potential, additional expenditure Craig would receive with an increase in local and publicly accessible recreation opportunities provided through the BLM's land acquisition. This paper also performs a sensitivity analysis to estimate economic contributions at lower levels of participation as compared to an estimated typical year. Using spending data combined with user responses, this paper seeks to provide key insights into user perceptions for consideration in future policy and management decisions impacting Moffat County's recreation and tourism economy, with insights important to greater Northwest Colorado as well.
Keywords: economic development; input output; tourism; economic impact; economic contribution; outdoor recreation